Ski area effects on headwater streamflow - Sidell, Marielle Alice, author; Kampf, Stephanie K., advisor; Fassnacht, Steven, committee member; Morrison, Ryan, committee member (Colorado State University. Libraries, 2022)
Colorado headwater streams produce water supply for the West. The effects of singular land use changes on headwater watersheds have been studied at length, but much less is known about the combined interactions of multiple land use changes on headwater streamflow generation. We examined how the interactions of three land use changes associated with ski area developments (tree clearing, trail and road building, and artificial snow application) affected streamflow at a ski area in northern Colorado. Our study area included three watersheds with stratified levels of development, within a United States Forest Service ski area permit boundary. Three main creeks and their tributaries were equipped with twelve pressure transducers scheduled for data collection at continuous 15 minute intervals over two water years beginning in late summer 2019. Burgess Creek (5.91 km2), which had the greatest degree of development and creek accessibility, was equipped with 9 data loggers; Priest Creek (2.35 km2) had two monitoring sites, and Beaver Creek (2.28 km2) had one. We initially performed an ANOVA comparison of our ski area stream data to two reference watersheds, Hot Spring Creek (14.87 km2) and Spring Creek (2.65 km2) and detected no significant differences in streamflow generation or timing. We then examined how streamflow generation and timing related to the degree of development and watershed characteristics using both univariate correlation analysis and multivariate models. Mean basin elevation was the most significant driver of the timing of flow delivery; development also plays an obvious role in both streamflow generation and timing. Total seasonal and annual streamflow generation increase significantly with development, and the timing of streamflow is earlier in the season in developed watersheds. Overall, this study shows that development affects how and when streamflow is generated from forested headwater stream systems, but our conclusions apply to just one ski area in northern Colorado. Long-term stream monitoring across watersheds with multiple disturbances, like those seen on ski resorts, should be a priority to understand how water delivery is affected by development.